2010
DOI: 10.2174/156800910791859461
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Apoptotic Signaling Pathways in Human Lung Cancer

Abstract: Lung carcinoma is the leading cause of carcinoma death in the world. Despite recent advances in understanding the molecular biology of lung cancer and the introduction of new therapeutic agents for its treatment, its dismal 5-year survival rate has not changed substantially. Clinical approaches have not significantly improved the survival of patients with advanced lung cancer. However, recent discoveries about the molecular mechanisms responsible for lung cancer initiation and proliferation have unveiled new t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 64 publications
0
26
0
Order By: Relevance
“…Imbalance of cell proliferation and apoptosis had been implicated in multiple cancers, including lung cancer, the most common one in human beings [1]. It is suggested that both genetic [2] and environmental [3] factors play critical roles in the etiology of lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Imbalance of cell proliferation and apoptosis had been implicated in multiple cancers, including lung cancer, the most common one in human beings [1]. It is suggested that both genetic [2] and environmental [3] factors play critical roles in the etiology of lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Despite recent advances in understanding the molecular biology of lung cancer and the introduction of new therapeutic agents for its treatment, its dismal 5-year survival rate has not changed substantially (1). Clinical approaches have not significantly improved the survival of lung cancer patients.…”
mentioning
confidence: 99%
“…Clinical approaches have not significantly improved the survival of lung cancer patients. However, recent discoveries regarding the molecular mechanisms responsible for lung cancer initiation and proliferation have unveiled new targets for therapy (1). Emerging evidence suggests that alterations in pro-and anti-apoptotic pathways are common in cancer cells, and defects in regulation of apoptosis have been implicated in tumorigenesis and drug resistance (1)(2)(3).…”
mentioning
confidence: 99%
“…Many cancer types also display intrinsic resistance to proapoptotic stimuli even before metastasising, including NSCLC (43)(44)(45), melanoma (46,47), pancreatic cancer (48,49), oesophageal cancer (50) and glioma (51,52). Apart from the lack of response to apoptotic drugs, many cancers also develop an acquired chemoresistance during chronic treatments: the multidrug resistance (MDR) phenotype, which is a phenomenon caused by decreased intracellular drug accumulation in the cancer cells due to enhanced drug efflux (53,54).…”
Section: Discussionmentioning
confidence: 99%
“…Of these eight cancer cell lines, we previously demonstrated high levels of resistance to pro-apoptotic stimuli for the human U373 and T98G glioblastoma cells (50,62), the A549 NSCLC (15,44) and the SKMEL-28 melanoma (47). In the same manner, we demonstrated the sensitivity to proapoptotic stimuli of the human MCF-7 breast cancer (63), the PC-3 prostate cancer (63), and the mouse B16F10 melanoma (47) cell lines.…”
Section: Discussionmentioning
confidence: 99%